2021
DOI: 10.1097/sap.0000000000002698
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphy to Evaluate Changes in Physical Activity After Autologous Breast Reconstruction

Abstract: Purpose Early ambulation and return to preoperative (baseline) ambulatory level is protective against postoperative venous thromboembolism. The duration of decreased physical activity after surgery is unknown for most procedures, as surgeons typically estimate physical recovery based on subjective patient reporting. This study aims to quantify the time it takes to return to baseline ambulatory status after breast reconstruction using actigraphy devices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 11 , 12 , 13 In a study involving adult hematopoietic stem cell transplant recipients, average daily steps were associated with increases in pain, fatigue, and gastrointestinal symptoms. 11 Similar studies have demonstrated altered activity patterns in cancer patients recovering postoperatively from surgery, 14 , 15 , 16 sickle cell patients experiencing painful vaso-occlusive crises, 17 and terminal cancer patients receiving pain medications. 18 Additionally, past research indicates that increased physical activity may be associated with long term benefits in cancer survivors, including improved quality of life and decreased cancer recurrence.…”
Section: Introductionmentioning
confidence: 73%
“… 11 , 12 , 13 In a study involving adult hematopoietic stem cell transplant recipients, average daily steps were associated with increases in pain, fatigue, and gastrointestinal symptoms. 11 Similar studies have demonstrated altered activity patterns in cancer patients recovering postoperatively from surgery, 14 , 15 , 16 sickle cell patients experiencing painful vaso-occlusive crises, 17 and terminal cancer patients receiving pain medications. 18 Additionally, past research indicates that increased physical activity may be associated with long term benefits in cancer survivors, including improved quality of life and decreased cancer recurrence.…”
Section: Introductionmentioning
confidence: 73%
“…ActiGraph technology is a tool that can help assess ergonomics; however, in most cases, patients undergoing different surgical procedures are below its scope. 31,32 In addition, no other specific algorithms or prior research related to actigraphy and liposuction were found.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Although these are positive outcomes, there remains significant postoperative abdominal donor-site morbidity, 5,6 including a decline in physical activity during the early postoperative period. 7 Efforts to reduce postoperative pain and opioid-dependence have led to the creation and widespread application of enhanced recovery after surgery (ERAS) pathways, which have helped decrease opioid use and reduce hospital stay and costs. 8 As part of the ERAS pathway, transversus abdominis plane (TAP) blocks are proven to reduce perioperative pain after abdominally based autologous breast reconstruction, and use of liposomal bupivacaine has been associated with reduced narcotic use after surgery.…”
mentioning
confidence: 99%
“…1,4 Although these are positive outcomes, there remains significant postoperative abdominal donor-site morbidity, 5,6 including a decline in physical activity during the early postoperative period. 7…”
mentioning
confidence: 99%